Revisiting the Trypanosoma cruzi metacyclogenesis: morphological and ultrastructural analyses during cell differentiation - Gonçalves, Camila Silva (Parasit Vectors, 2018)
BACKGROUND: Trypanosoma cruzi uses several strategies to survive in different hosts. A key step in the life-cycle of this parasite is metacyclogenesis, which involves various morphological, biochemical, and genetic changes that induce the differentiation of non-pathogenic epimastigotes into pathogenic metacyclic trypomastigotes. During metacyclogenesis, T. cruzi displays distinct morphologies and ultrastructural features, which have not been fully characterized. RESULTS: We performed a temporal description of metacyclogenesis using different microscopy techniques that resulted in the identification of three intermediate forms of T. cruzi: intermediates I, II and III. Such classification was based on morphological and ultrastructural aspects as the location of the kinetoplast in relation to the nucleus, kinetoplast shape and kDNA topology. Furthermore, we suggested that metacyclic trypomastigotes derived from intermediate forms that had already detached from the substrate. We also found that changes in the kinetoplast morphology and kDNA arrangement occurred only after the repositioning of this structure toward the posterior region of the cell body. These changes occurred during the later stages of differentiation. In contrast, changes in the nucleus shape began as soon as metacyclogenesis was initiated, while changes in nuclear ultrastructure, such as the loss of the nucleolus, were only observed during later stages of differentiation. Finally, we found that kDNA networks of distinct T. cruzi forms present different patterns of DNA topology. CONCLUSIONS: Our study of T. cruzi metacyclogenesis revealed important aspects of the morphology and ultrastructure of this intriguing cell differentiation process. This research expands our understanding of this parasite’s fascinating life-cycle. It also highlights the study of T. cruzi as an important and exciting model system for investigating diverse aspects of cellular, molecular, and evolutionary biology.